STUDY ON EFFECT OF DIFFERENT ORGANICS ON YIELD AND QUALITY OF ORGANICALLY GROWN ONION - V. R. NAIK,; P. B. PATEL,; B. K. PATEL, (The Bioscan, 2014)
A field experiment to study the effect of different organic sources of nutrients on growth and yield of drip irrigated onion Cv. Nasik Red was carried out on organic plot (conversion phase) at Coastal Soil Salinity Research Station, Danti-Umbharat (Navsari Agricultural University, Gujarat) during rabi 2009-10 to 2011-12. In all seven treatments viz., T1: FYM, T2: Bio-compost, T3: Vermi-compost, T4: FYM (50 % basal) + Castor cake (50 % top dressing), T5: Bio-compost (50 % basal) + Castor cake (50 % top dressing), T6: Vermi-compost (50 % basal) + Castor cake (50 % top dressing) and T7: IBNM along with one control (INM – outside organic plot) were tested in RBD with four replications. The results revealed that leaf length and average bulb weight as well as bulb yield of onion were significantly higher when FYM, bio-compost and vermin-compost were applied in combination with castor cake than their individual application. With respect to control v/s rest analysis, effect on leaf length was not significant, while control treatment (INM) registered significantly higher average bulb weight of onion as compared to treatment mean. Control v/s rest analysis was not found significant on bulb yield of onion. Organically treated plot recorded significantly lower storage losses as compared to control treatment. After three year of experiment at fixed site, decrease in pH and EC and improvement in soil fertility and finer and coarser fraction of water stable aggregates was recorded in all the treatments received organic sources of nutrients as compared to plots received the INM treatment.